Simple Machines - Canizares, Susan; Nang Chan Yeema (New York, USA Scholastic Inc., 1999)
Rhyming text and photographs explore the many tasks that can be performed by such simple machines as springs, ramps, and pulleys.
Keywords: Juvenile Nonfiction